The Supply of Public School Teachers to An Urban Metropolitan Area: A Possible Source of Discrimination in Education - Toder, Eric J. (The Review of Economics and Statistics, 1972)
Eric J. Toder, The Supply of Public School Teachers to An Urban Metropolitan Area: A Possible Source of Discrimination in Education, The Review of Economics and Statistics, Vol. 54, No. 4 (Nov., 1972), pp. 439-443